The Role of Islamic Religious Education In Shaping Student Muslim Personality: The Role of Islamic Religious Education In Shaping Student Muslim Personality - Alim, Syaiful (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2020)
Humans as caliphs on this earth need to place themselves along their nature. Al-Quran is a source of direction, how a Muslim chooses the method of movement according to the will of Allah SWT. He knows better what good people need to fulfill their desires, namely the safety and welfare of their lives in this world and the hereafter. In order to achieve that, Allah SWT sent down commands and prohibitions in various forms for humans which are stated in the Qur'an explicitly and implicitly. All forms of prohibitions and orders are measured in such a way that they are all in accordance with the human capabilities themselves. Since the beginning, Islamic religious education is an effort to grow and strengthen the tendency of tawhid which has become human nature. Religion is a guide and guide in the right direction. Because the human personality includes three aspects, namely the physical, psychological and spiritual aspects, it will be something very important for human life if it is based on the basis of religion. Therefore, religious education plays a very important role in shaping a person's personality, especially Muslim personality, the more so religious education is given intensively and continuously. Because basically having a good personality is everyone's dream. Because with that, he will be respected, respected and loved by those around him.